Evaluation of Drastic and Geograpidc Information System as a Tool in Determining the Groundwater Quality Vulnerability of Kuala Langat Aquifer - Hii, Ching Poon (2002)
This thesis describes the results of a ground water pollution potential modeling, which examined the entire Kuala Langat aquifer using GIS. The pollution potential model implemented within GIS is known as DRASTIC, a model, which was developed by the u.S. Environmental Protection Agency in 1985. In compiling a groundwater vulnerability map of Kuala Langat, it was decided to use the widely known DRASTIC methodology that includes Depth to groundwater, Recharge due to rainfall, Aquifer media, Soil media, Topography, Impact of the vadose zone, and Conductivity (hydraulic). Although not designed for a GIS, this model represents a classic spatial analysis approach for which GIS have become known. This thesis outlines the techniques used in compiling the data sets for those factors that influence the susceptibility of groundwater contamination over Kuala Langat and the techniques involved In manipulating and displaying these data in a GIS. The different techniques employed in the gathering and calculations of the different information sets required by the DRASTIC model to describe the groundwater vulnerability are presented in detail. The final output, which is in the form of a color paper map, will be useful in presenting the concept of groundwater vulnerability and groundwater protection to the layman. Results show that DPPI ranges from 80 to 165 giving 90% of the entire area as moderate vulnerable. However the south and east portion of Kuala Langat pose much more pollution potential than other area. Pesticide DPPI ranges from 1 14 to 166 with higher numbers representing higher pollution potential, indicating that moderate pesticide pollution potential occurs through out the entire Kuala Langat aquifer. The Pesticide DRASTIC Pollution Potential Index of Kuala Langat is higher than DRASTIC Pollution Potential Index (DPPI) of Kuala Langat. From these findings, it can be concluded that the potential source of pollution in the area derived from agricultural activities.